2016
DOI: 10.1002/acp.3248
|View full text |Cite
|
Sign up to set email alerts
|

Does Poor Understanding of Physical World Predict Religious and Paranormal Beliefs?

Abstract: SummaryAlthough supernatural beliefs often paint a peculiar picture about the physical world, the possibility that the beliefs might be based on inadequate understanding of the non‐social world has not received research attention. In this study (N = 258), we therefore examined how physical‐world skills and knowledge predict religious and paranormal beliefs. The results showed that supernatural beliefs correlated with all variables that were included, namely, with low systemizing, poor intuitive physics skills,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Likewise, we can assess PBrelated behavior with cognitive measures that have previously been associated with enhanced PBs. Examples of such measures include (1) tasks that show a tendency to easily associate things or events (Bressan, 2002;Rogers, Fisk, & Wiltshire, 2011;Rogers, Qualter, & Wood, 2016), (2) the propensity to see meaningful patterns in random noise (Blackmore & Moore, 1994;Brugger et al, 1993;Riekki, Lindeman, Aleneff, Halme, & Nuortimo, 2013), (3) attenuated reasoning abilities (Denovan, Dagnall, Drinkwater, & Parker, 2018;Lawrence & Peters, 2004;Lindeman & Svedholm-Häkkinen, 2016), and (4) repetition avoidance (Brugger, Landis, & Regard, 1990). Brugger et al (1990) assessed repetition avoidance by asking participants to repeatedly imagine throwing a dice and to report the number they imagined on top of the dice (mental dice task).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, we can assess PBrelated behavior with cognitive measures that have previously been associated with enhanced PBs. Examples of such measures include (1) tasks that show a tendency to easily associate things or events (Bressan, 2002;Rogers, Fisk, & Wiltshire, 2011;Rogers, Qualter, & Wood, 2016), (2) the propensity to see meaningful patterns in random noise (Blackmore & Moore, 1994;Brugger et al, 1993;Riekki, Lindeman, Aleneff, Halme, & Nuortimo, 2013), (3) attenuated reasoning abilities (Denovan, Dagnall, Drinkwater, & Parker, 2018;Lawrence & Peters, 2004;Lindeman & Svedholm-Häkkinen, 2016), and (4) repetition avoidance (Brugger, Landis, & Regard, 1990). Brugger et al (1990) assessed repetition avoidance by asking participants to repeatedly imagine throwing a dice and to report the number they imagined on top of the dice (mental dice task).…”
Section: Introductionmentioning
confidence: 99%
“…The positive relationship between Faith in Intuition and paranormal beliefs has typically been strong, with correlations usually ranging from .35 to .50. The association between need for cognition and paranormal beliefs is negative but weaker, with correlations seldom reaching a value higher than -.25 (e.g., Epstein et al, 1996;Lindeman & Svedholm-Häkkinen, 2016;Lobato, Mendoza, Sims, & Chin, 2014;.…”
mentioning
confidence: 99%
“…Others have suggested that a poor understanding of the physical world and intuitive thinking styles correlate with an acceptance of paranormal and religious explanations over scientific explanations (Lindeman and Svedholm-Häkkinen 2016). The process skills involved in science have been defined in many different ways, including scientific process skills (OECD 1999), procedural skills (e.g., Gott and Duggan 1994), experimental and investigative science (National Curriculum;DOE 1995), habits of mind (AAAS 1993), scientific inquiry abilities (National Academy of Sciences 1994), scientific reasoning skills (Lawson et al 2000), or critical thinking skills (Bransford et al 2000;NSF 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Religious views, while an integral part of our cultural richness, have been negatively associated with the acceptance of evolution in several studies (Anderson 2007;Andersson and Wallin 2006) and a poorer understanding of the physical world (Lindeman and Svedholm-Häkkinen 2016). For individuals who have a strong religious background, science instructors may face difficulty overcoming these barriers using existing pedagogical approaches.…”
Section: Introductionmentioning
confidence: 99%